Effects of Substituents on Synthetic Analogs of Chlorophylls. Part 4: How Formyl Group Location Dictates the Spectral Properties of Chlorophylls b, d and f. (12th January 2015) - Yuen, Jonathan M.; Harris, Michelle A.; Liu, Mengran; Diers, James R.; Kirmaier, Christine; Bocian, David F.; Lindsey, Jonathan S.; Holten, Dewey
Abstract Photosynthetic organisms are adapted to light characteristics in their habitat in part via the spectral characteristics of the associated chlorophyll pigments, which differ in the position of a formyl group around the chlorin macrocycle (chlorophylls b, d, f) or no formyl group (chlorophyll a). To probe the origin of this spectral tuning, the photophysical and electronic structural properties of a new set of synthetic chlorins are reported. The zinc and free base chlorins have a formyl group at either the 2‐ or 3‐position. The four compounds have fluorescence yields in the range 0.19–0.28 and singlet excited‐state lifetimes of ca 4 ns for zinc chelates and ca 8 ns for the free base forms. The photophysical properties of the 2‐ and 3‐formyl zinc chlorins are similar to those observed previously for 13‐formyl or 3, 13‐diformyl chlorins, but differ markedly from those for 7‐formyl analogs. Molecular‐orbital characteristics obtained from density functional theory (DFT) calculations were used as input to spectral simulations employing the four‐orbital model. The analysis has uncovered the key changes in electronic structure engendered by the presence/location of a formyl group at various macrocycle positions, which is relevant to understanding the distinct spectral properties of the natural chlorophylls a, b, d and f.